PELAKSANAAN PENGELOLAAN SEBAGAI UPAYA PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK PADA MASA PANDEMI COVID 19 DI SDN DUREN IV KLARI, KARAWANG - Lilis Karyawati; Nia Karnia; Halimatussa’diyah Gunawan (Hijri, 2023)
School is a very important facility for ongoing teaching and learning activities. Therefore, good, effective and efficient classroom management is needed so that teaching and learning activities can run well and educational goals can be achieved. The teacher is an important component in education, because students don't like or like a lesson depending on how the teacher teaches. Competent teachers will be better able to create an effective, enjoyable learning environment, and will be better able to manage their classes so that student learning is at an optimal level. Each teacher has a different level of education and teaching experience so that the perspective and management of the class are in accordance with the competencies they have. SDN Duren IV has tried to manage classes properly and optimally during the Covid 19 pandemic, namely by conducting home visits at the start of the Covid 19 pandemic, this was carried out so that the learning process could take place effectively. Over time, classroom management models such as online have been created (forming Whatsup groups, Whatsaap video calls that are carried out in groups and Google classroom). Classroom management carried out at SDN Duren IV varies, meaning that each teacher uses a type of classroom management according to the abilities and characteristics of the students in their class. This is done with the aim that students are able to follow the learning conducted by the teacher and can make students active in the learning. So that even during the Covid 19 pandemic the predetermined learning objectives could be achieved. Student achievement has not decreased, but the increase in achievement is still there, although not as maximal as before the Covid 19 pandemic. Based on this background, the aim of this research is to describe classroom management during the Covid 19 pandemic in improving student achievement at SDN Duren IV, supporting factors and inhibiting classroom management .Keywords:Classroom Management, Learning Achievement, and the Covid 19 Pandemic.